Reaching rural communities with culturally appropriate care: a model for adapting remote monitoring to American Indian veterans with posttraumatic stress disorder - Brooks, Elizabeth; Novins, Douglas K; Noe, Tim; Bair, Byron; Dailey, Nancy; Lowe, Jeff; Richardson, Jr, W J Buck; Hawthorne, Kara; Shore, Jay H (Telemedicine journal and e-health, 2013)
Providing specialized healthcare to rural communities can be extremely difficult, and consequently many health organizations are turning to the use of telehealth technologies for care delivery. One such technology, remote monitoring, has been successfully implemented with patients suffering from chronic and other medical conditions. A drawback, however, is that remote monitoring devices are programmed to reach a broad audience, and consequently the content may not be suitable for all patients-especially those who are not a part of the dominant culture. This report provides a model for adapting remote monitoring to specific populations who are undergoing care for posttraumatic stress disorder. Adaptation changes focus on (1) information gathering, (2) process and dialogue changes, (3) testing, and (4) patient and administrative feedback. Data for such modifications were gathered through a series of community meetings, patient interviews, and provider feedback. A case example highlights the successful implementation of the adaptation model for a rural American Indian Veteran population. Patients showed high acceptability of both the programmatic and cultural adaptations. Feasibility of the program also appeared positive, with most patients reporting that the readability of the program was appropriate, the dialogue duration was not burdensome, and technical problems were rare. Remote monitoring provides the ability to be modified for use with certain subpopulations. Procedural recommendations in this report highlight special considerations for working with American Indians living on or near reservation areas, although the model can be broadly adapted to several groups.